Hubungan Pengetahuan, Sikap, dan Persepsi Pasien HIV/AIDS terhadap Pencegahan Penularan - Ari Rahmat Aziz; Jannaim Jannaim; Rohmi Fadli (Universitas Malahayati, 2023)
ABSTRACT Human Immunodeficiency Virus (HIV) / AIDS infection was increased every year. One of the causes of new sufferers is the risky sexual behavior people with HIV / AIDS. The purposed of this study is to analyze the Determinant of risk prevention behavior of transmission people with HIV / AIDS in Arifin Achmad Public Hospital.The research method used cross-sectional study to describe the determinant of prevention of transmission of HIV / AIDS. The research sample was 83 respondents. The study was conducted from Jun 2, 2021 to July 2, 2021 in Arifin Achmad Public Hospital. The results showed that of 83 respondents, 26 (31%) respondents had risky behavior and 57 (68%) respondents had healthy behavior. Analyze with statistics showed there are not correlation between Knowledge (p value = 0.119) with prevention of transmission HIV AIDS patient. There are correlation between attitude (0.015), perception (0.009) with prevention of transmission HIV/ AIDS. These results encourage care giver to be more active in providing health education. Keywords: Sexual Behavior, HIV/ AIDS Patient, Transmission Prevention ABSTRAK Infeksi Human Immunodeficiency Virus (HIV)/AIDS meningkat setiap tahunnya. Salah satu penyebab munculnya penderita baru adalah perilaku seksual berisiko penderita HIV/AIDS.Tujuan penelitian ini adalah menganalisis Determinan perilaku pencegahan risiko penularan HIV/AIDS di RSUD Arifin Achmad. Metode penelitian yang digunakan adalah cross-sectional study untuk mendeskripsikan determinan pencegahan penularan HIV/AIDS. Sampel penelitian sebanyak 83 responden. Penelitian dilakukan pada tanggal 2 Juni 2021 sampai dengan 2 Juli 2021 di RSUD Arifin Achmad. Hasil penelitian menunjukkan bahwa dari 83 responden, 26 (31%) responden berperilaku berisiko dan 57 (68%) responden berperilaku sehat. Analisis dengan statistik menunjukkan tidak ada hubungan antara Pengetahuan (p value = 0,119) dengan pencegahan penularan HIV AIDS pasien. Ada hubungan antara sikap (0,015), persepsi (0,009) dengan pencegahan penularan HIV/AIDS. Hasil ini mendorong care giver untuk lebih aktif dalam memberikan pendidikan kesehatan Kata kunci: Perilaku Seksual, Pasien HIV/ AIDS, Pencegahan Penularan